An Examination of Stress and Burnout in Certified Athletic Trainers at Division I-A Universities - Hendrix, Amy E. (2000)
OBJECTIVE: A growing body of knowledge indicates that too much stress can negatively influence psychological and physical health. A model proposed by Smith to explore personal and situational variables, stress appraisal, and burnout has led to significant understanding of burnout of individuals working in service professions. We examined the relationship of hardiness, social support, and work-related issues relevant to athletic trainers to perceived stress and the relationship of perceived stress to burnout. DESIGN AND SETTING: Correlational analyses were performed to examine the relationships predicted by Smith's model. In addition, we conducted stepwise multiple regression analyses to assess the relative contributions of the personal and situational variables to perceived stress and to examine the relative impact of perceived stress on 3 burnout factors (emotional exhaustion, personal accomplishment, and depersonalization). SUBJECTS: One hundred eighteen certified athletic trainers working in National Collegiate Athletic Association Division I-A intercollegiate settings that maintain a football program. MEASUREMENTS: We assessed personal and situational variables using the Hardiness Test, the Social Support Questionnaire, and the Athletic Training Issues Survey, adapted for this study. The Perceived Stress Scale was used to assess stress appraisal, and the Maslach Burnout Inventory was used to assess 3 dimensions of burnout. RESULTS: Our results were in support of Smith's theoretical model of stress and burnout. Athletic trainers who scored lower on hardiness and social support and higher on athletic training issues tended to have higher levels of perceived stress. Furthermore, higher perceived stress scores were related to higher emotional exhaustion and depersonalization and lower levels of personal accomplishment. CONCLUSIONS: Our findings examining burnout in Division I athletic trainers were similar to those of other studies investigating coaches and coach-teachers and in support of Smith's theoretical model of stress and burnout.